De novo design of self-assembly hydrogels based on Fmoc-diphenylalanine providing drug release. Issue 41 (7th October 2021) - Li, Xiang; Zhang, Huijun; Liu, Lingyan; Cao, Chunyan; Wei, Peng; Yi, Xin; Zhou, Yifeng; Lv, Qingyang; Zhou, Dongfang; Yi, Tao
Abstract : We report a self-assembly hydrogel formed under mild conditions based on Fmoc-FF by modifying its hydrophilicity. The hydrogel is elastic, reversible and injectable and can be used as a carrier to carry drugs into cancer cells. Abstract : Short peptides with self-assembled nanostructures are widely applied in the areas of drug delivery systems and biomaterials. In this article, we create a new peptide-based hydrogelator (Fmoc-FFRRVR) based on N -fluorenylmethoxycarbonyl-diphenylalanine (Fmoc-FF) through an approach to improve its hydrophilicity. Compared to Fmoc-FF, Fmoc-FFRRVR prefers to form a hydrogel under mild conditions, and the gelation time is only 2 s. Fmoc-FFRRVR self-assembles into organized arrays of β-sheets in nanofibers via π-stacking of Fmoc-FF, which are supported by circular dichroism and fluorescence emission spectroscopy. Rheology results confirm that the hydrogel of Fmoc-FFRRVR is elastic, reversible and injectable. The newly discovered hydrogel not only retains some excellent performances of Fmoc-FF, but also can be used as a drug carrier for biomedical applications.